MECHANISM OF WATER MASS CIRCULATION IN THE AMBON BAY USING DENSITY ASSIMILATION MODEL - CORVIANAWATIE ( NIM : 22413002 ); Pembimbing : Dr. rer. nat. Mutiara Rachmat Putri, CORRY
Ambon Bay is separated into Inner Ambon Bay (IAB) and Outer Ambon Bay (OAB) by sill (12m). Previous study in this area stated that upwelling on southeast monsoon bring the Banda Sea water mass reach the IAB. In this research we did 3D hydrodynamic simulation (baroclinic mode) for Juni until Oktober 2008 to understand these phenomena. This simulation is using tides and density as a driving force. Verification of model result towards observation data shows that the model canÃ‚Â’t simulate upwelling phenomena. So that data assimilation technique using Successive Cressman Correction method is used in this research. Numerical model with data assimilation minimize the mean rmse about 0.13% for current velocity and 33.1% for ocean density. Based on those result known that circulation in the Ambon Bay dominated by tides and surface density gradient. Surface density gradient conducting the vertical mixing in the OAB, then tidal wave and currents help the water mass in OAB passing through the sill into IAB.